Effect of reaction parameters on the decarboxylation of oleic acid over Pt/ZIF‐67membrane/zeolite 5A bead catalysts. Issue 1 (20th October 2016) - Yang, Liqiu; Carreon, Moises A
Abstract: BACKGROUND: Carboxylic acids obtained from biomass raw materials are attractive starting chemicals in the conversion to linear, paraffinic hydrocarbons. The resultant hydrocarbon products can be used as platform chemicals for the production of fuels, lubricants and other valuable chemicals. RESULTS: The effects of reaction parameters on the decarboxylation of oleic acid to paraffins, and hydrocarbons over Pt supported on zeolite 5A beads coated with ZIF‐67 membrane (Pt/ZIF‐67 membrane/zeolite 5A) were investigated. Almost complete conversion of oleic acid was observed for all reaction conditions studied here. The catalysts displayed high selectivity to heptadecane even with as low as 0.5 wt% Pt loading. Moderate reaction temperature and pressure were favorable to obtain high yield of heptadecane. The catalysts displayed a slight decrease in catalytic activity after recycling. Interestingly, of all explored reaction conditions, the catalysts exhibited the highest selectivity to heptadecane (∼91%) in the presence of CO2 . CONCLUSION: The results from this work demonstrate that the studied reaction parameters greatly affected the overall catalytic performance (mainly product distribution) for the decarboxylation of oleic acid into heptadecane over Pt/ZIF‐67 membrane/zeolite 5A catalysts. © 2016 Society of Chemical Industry